Hubungan antara Body Image dan Subjective Well-Being Pada Remaja Putri - Tesi Saktiva Alwis; Jimmy Ellya Kurniawan (Universitas Ciputra Surabaya, 2018)
The assessment of body shape or often called the body image is very common among female adolescents. Previous studies showed the body image greatly affected the psychological well-being of adolescents. Young women who considered themselves people with worse body tended to undergo depression. This perception is likely to inhibit their subjective well-beings. In reality, the body image did not affect subjective well-being of the individual. This research aims to investigate the relations between body image and subjective well-being in adolescent girls. This research is a correlational quantitative study. The subjects consisted of 175 Faculty of Fashion and Design Business of